A Position in the Field: Aboriginal Experiences of Cricket in Western Australia - Chadwick, Ross Raymond (Curtin University, 2017)
This thesis explores the ways in which individuals make sense of and engage with social fields; revealing the role of habitus and disposition as animators of social experience and the field as lived experience that endures in memory, narrative and embodied practice. I show how ethnographic interviews, and their capacity to invoke the field and its contexts, are an effective way of engaging anthropologically with narrative lives, as a rich resource for exploring social practice.